Smart work centralise, organise, realise : how to boost your productivity in 3 easy steps - Crowley, Dermot (John Wiley & Sons Australia, Ltd, 2016)
Organise your way to renewed focus and calm Smart Work is the busy professional's guide to getting organised in the digital workplace. Are you drowning in constant emails, phone calls, paperwork, interruptions and meeting actions? This book throws you a lifeline by showing you how to take advantage of your digital tools to reprioritise, refocus and get back to doing the important work. You may already have the latest technology, but if you're still swamped, you're not using it to your advantage. This useful guide shows you how to leverage the technology you have to centralise your work into one integrated tool. You'll develop a simple and sustainable productivity system to organise your actions, manage your inputs and achieve your outcomes. The highly visual nature of the book helps you quickly grasp the ideas you need most. Like most professionals, you want to do great work and achieve great things. But when half your day is spent on emails, phone calls and 'extra' duties, you rarely get a chance to shine. This book changes that. Get back in control so you can start performing like a star.